2014
DOI: 10.1186/s12983-014-0082-9
|View full text |Cite
|
Sign up to set email alerts
|

Sensing deep extreme environments: the receptor cell types, brain centers, and multi-layer neural packaging of hydrothermal vent endemic worms

Abstract: IntroductionDeep-sea alvinellid worm species endemic to hydrothermal vents, such as Alvinella and Paralvinella, are considered to be among the most thermotolerant animals known with their adaptability to toxic heavy metals, and tolerance of highly reductive and oxidative stressful environments. Despite the number of recent studies focused on their overall transcriptomic, proteomic, and metabolic stabilities, little is known regarding their sensory receptor cells and electrically active neuro-processing centers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…Studies have consistently demonstrated an association between SES and child physical health. Children living in poverty are at a higher risk of low birth weight ( Rouse et al , 2015), child mortality ( Shigeno et al ., 2014) and poor nutritional status ( Braissant et al ., 2015; Liu et al , 2015). These children consequently suffer poorer neurodevelopmental outcomes than those who are from wealthier families ( Kordas et al ., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have consistently demonstrated an association between SES and child physical health. Children living in poverty are at a higher risk of low birth weight ( Rouse et al , 2015), child mortality ( Shigeno et al ., 2014) and poor nutritional status ( Braissant et al ., 2015; Liu et al , 2015). These children consequently suffer poorer neurodevelopmental outcomes than those who are from wealthier families ( Kordas et al ., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In the vestimentiferan Oasisia , the amp and SLN were also detected as P-medN and vCS , respectively (Fig 5a in [23]). Mushroom bodies are found in many errant and in some sedentary annelids such as the serpulid Serpula , the alvinellid Paralvinella hessleri , and sabellids, including Chone and Euchone species [49,64,80,83]. As in P .…”
Section: Discussionmentioning
confidence: 99%
“…As in P . hessleri [83] and E . papillosa [49], the mushroom-like structures in Riftia do not occupy the typical dorso-lateral position in the brain, but instead extend anteriorly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the famous 'Pompeii worm' Alvinella pompeijna and the 'Sulfur worm' Paralvinilla sulfincola, P. hessleri also colonizes mid to high temperature hydrothermal vent. It is considered to be among the most thermotolerant metazoan (Shigeno et al 2014). However, the molecular information of the P. hessleri (as well as most other alvinellid worms) is still extremely rare.…”
mentioning
confidence: 99%